“Don't touch”: Negotiating the boundaries of acceptable touching in classrooms - Karvonen Ulla; Routarinne Sara; Tainio Liisa (Elsevier Ltd, 2025)
In peer interactions within educational settings, students touch each other to display affection, to build a sense of togetherness and to manage each other's participation. On the other hand, embodied acts between students can also be physically forceful, embarrassing, or feel uncomfortable. While certain touch types such as caressing, stroking and tapping are typically associated with displays of affection, all touches are situated, and participants locally negotiate their meanings, functions, and appropriateness. In this article, we examine how boundaries of acceptable touch and rights to touch others are locally negotiated in the classrooms. We analyze three episodes in which the touch-recipient or a bystanding teacher rejected an affectionate student-to-student touch, and the rejection included a verbal description that portrayed the touch as a violation, thus assigning a moral meaning to the tactile act. The data for the study consists of video-recorded classroom interaction, and multimodal conversation analysis is used as the method for analyzing the data. Our analysis shows that in these episodes, two kinds of moral orders were invoked: a more universal one that demands respect for a person's bodily integrity and an institutional one that demands students to maintain an orderly classroom by refraining from disturbing the other's engagement in pedagogical activities.